Farm work science facing the challenge of the XXI century : Proceedings XXIX CIOSTA-CIGR V Congress - Juliszewski, T., (Biology - Book Archive 2000-2006., 2001)
This publication contains the papers presented at the XXIX CIOSTA - CIGR V International Congress held in June 2001 in Cracow, Poland. The Congress was held under the auspices of the Agricultural University of Cracow, the Agricultural Engineering Committee of the Polish Academy of Sciences and the Polish Association of Agricultural Engineering.These proceedings deal with a broad spectrum of topics which modern agriculture had to confront with the arrival of the new century. Knowledge and ideas were exchanged on a highly international level (21 participating countries) on problems of adjustment to contemporary economic requirements, electronic technology, work conditions and organisation management, ergonomics, system engineering and farm techniques in modern agriculture. Special consideration has been given to the adjustment of agriculture to contemporary economic challenges, as well as to modern aspects of electronic agricultural technology.By observing where agricultural science and research are going at the turn of the century, this book will help not only the specialist who wants a broader view on the scientific organization of farm work in general, but as well the reader who wants an overview on modern agriculture.